Tropical Sovereignty and Climate Governance: Brazil–Indonesia South–South Cooperation in Implementing Nationally Determined Contributions - Maryann Schoenberg (Universitas Muhammadiyah Jakarta, 2025)
This article examines Brazil–Indonesia climate cooperation as a strategic model of South–South governance among tropical forest countries. Both states occupy pivotal positions in global climate politics because of their extensive biodiversity, large land-use sectors, growing economies, and shared demand for climate justice within the Paris Agreement. Using a qualitative policy analysis of national climate commitments, diplomatic agendas, and contemporary debates on forest governance, the study argues that cooperation between Brazil and Indonesia should move beyond symbolic solidarity toward an implementation-oriented framework. The proposed framework contains five mutually reinforcing pillars: forest and land-use governance, Nationally Determined Contribution implementation and transparency, climate finance and investment diplomacy, low-carbon productive transformation, and just transition with social inclusion. The analysis shows that Brazil’s renewed ecological transformation agenda and Indonesia’s long-term low-carbon development strategy create complementary opportunities for policy learning, technical exchange, and joint advocacy in international negotiations. However, effective cooperation requires stronger institutional coordination, credible emissions data, safeguards for Indigenous peoples and local communities, and financial mechanisms that reduce the asymmetry between climate ambition and domestic development constraints. The article contributes to climate governance scholarship by conceptualising tropical sovereignty not as resistance to global norms, but as a basis for credible, equitable, and development-sensitive climate action. It concludes that Brazil–Indonesia cooperation can strengthen the political voice of the Global South while producing practical pathways for deforestation reduction, green industrialisation, and socially legitimate climate transitions across emerging economies facing similar ecological and fiscal vulnerabilities today globally.